2004
DOI: 10.1111/j.1365-2893.2004.00531.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of subgenomic hepatitis C virus RNA in Huh‐7 cells: ribavirin induces mutagenesis in HCV RNA

Abstract: Hepatitis C virus (HCV) infection is a major problem throughout the world. Combination therapy of interferon (IFN) and ribavirin is the best treatment for eradication at present, but the mechanism is not completely understood. We used the HCV replicon system to investigate this mechanism. The effects of six drugs (UDCA, glycyrrhizin, TJ-9, bezafibrate, ribavirin, and alpha-IFN 2b) on HCV subgenomic RNA (genotype 1b, NS5B 415Y) were examined by reverse transcription polymerase chain reaction, cloning and sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 48 publications
1
46
2
Order By: Relevance
“…However, combined with IFN, ribavirin enhanced the IFN effect by 1.46-to 1.62-fold; this boost may be crucial to clear the virus and may improve the efficacy of IFN therapy. Several previous reports have described increases in mutation frequencies induced by ribavirin (4,13,18,28). However, this mutagen effect of ribavirin was not detected in this study.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…However, combined with IFN, ribavirin enhanced the IFN effect by 1.46-to 1.62-fold; this boost may be crucial to clear the virus and may improve the efficacy of IFN therapy. Several previous reports have described increases in mutation frequencies induced by ribavirin (4,13,18,28). However, this mutagen effect of ribavirin was not detected in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…Using this replicon system, the anti-HCV effects of IFN and ribavirin have been evaluated (13,18,28,33). However, a number of these previous studies could not observe the anti-HCV effect of ribavirin in lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies using HCV replication models, mutagenic effects of ribavirin have been identified by several 54,[56][57][58][59][60] but not all authors. 61 When infectivity was used as a functional readout for mutagenesis, diminished infectivity was found with ribavirin treatment of HCV cultures.58 , 60 The concentrations of ribavirin needed to achieve mutagenic effects were high (up to 400 uM) and may exceed those achieved in vivo.…”
Section: Ribavirin: Mechanism Of Action Clinical Insightsmentioning
confidence: 99%
“…The region of the viral genome that codes for NS5B has been described as an important target in therapy with IFN and rBV (Kukolj et al 2005, Lu et al 2007, Lutchman et al 2007). The mechanisms that lead to viral resistance after IFN/ rBV treatment is still a matter of debate (Horiike et al 1999, Hadziyannis et al 2004, Kanda et al 2004, Hamano et al 2005, Hofmann et al 2007, Chung et al 2008, Kuntzen et al 2008, Kwong et al 2008, Nakamura et al 2008, Cannon et al 2009, Gaudieri et al 2009, rydberg et al 2009). For instance, Nelson et al (1995) showed that the mutations that occur in the HCV gene that codes for NS5B did not correlate with response to INF therapy, but Japanese studies associated IFN-rBV failure with mutations in the NS5B gene (Hamano et al 2005, Hmwe et al 2010 and Kuntzen et al (2008) showed that mutations conferred resistance to specifically targeted antiviral therapy drugs in treatmentnaïve patients infected with HCV genotype 1.…”
mentioning
confidence: 99%